(untitled) (Indian Journal of Forensic Medicine & Toxicology, 2020)
Introduction: Sleep disorders are very frequent among general population. The prevalence of sleep disturbances varies between 25 and 45%. Types of sleep abnormalities in which snoring is the common among all the adults. Oropharyngeal exercises are new, non-invasive, cost effective treatment modality for individuals having risk of obstructive sleep apnea, daytime sleepiness and snoring. Methods: The study design was systematic review and it includes studies from databases of PUBMED, MEDLINE, Cochrane library, SCOPUS, Science direct, and Google scholar (2002-2017). Result: Total 14 relevant articles were under taken. Studies included are related to prevalence, assessment, effect of different modalities and oropharyngeal exercises on daytime sleepiness, snoring and risk of obstructive sleep apnea and excludes those studies that involve other sleep disorders like insomnia, narcolepsy and circadian rhythm disorder etc. Abstracted information is related to their design, population characteristics, intervention and outcomes. Conclusion: Oropharyngeal exercises are effective in reducing the daytime sleepiness, snoring and risk of obstructive sleep apnea among adults having snoring. Several studies came out with the result that oropharyngeal exercises are beneficial in reducing sleep disorders.